Graphene modified electrodes for enhanced electrochemical detection - Walch, Nicholas John (Cranfield University, 2016)
The ability to inexpensively and reliably detect organic compounds is important across a multitude of different areas of science. Benzene ring functional groups are found in a wide variety of biological molecules, (such as amino acids, DNA nucleotide bases and blood based components). The qualification and quantification of these compounds in a sample has been achieved by techniques such as high performance liquid chromatography (HPLC), gas chromatography (GC), mass spectrometry (MS) and nuclear magnetic resonance (NMR), amongst others. These techniques, however, often require cumbersome, expensive equipment along with exhaustive sample preparation techniques and are thus not necessarily suitable for portable in-situ analysis of these compounds. This thesis details the fabrication and characterisation of graphene modified electrodes that show an increased sensitivity towards biomolecular compounds such as dopamine, amino acids, and DNA. The graphene was synthesised using a novel semi-automated method which was performed using a bespoke apparatus designed to alleviate the labour involved in synthesising graphene by the sonochemical method. The method involved pumping an aqueous solution of the surfactant into a solution of graphite in water which was under constant sonication. When used in an electrochemical system employing cyclic voltammetry the graphene modified electrodes showed not only a lower limit of detection in all cases, but also a shift in peak position which allowed for simultaneous quantification of mixtures of compounds. This could not be achieved with screen printed carbon electrodes alone as different peaks often occur at similar potentials, making it difficult or impossible to quantify these compounds individually. Slower scan rates can often give rise to separate peaks, however this adds time to the experiment which is not necessary with graphene modification. The binding interactions of novel resorcinarene molecules were also predicted by molecular modelling techniques and then confirmed using NMR binding experiments. The resorcinarene was tested against a range of different analytes and showed a degree of specificity. The interaction between the two surfactant molecules and the graphene surface was also analysed to determine whether or not the resorcinarene molecules could be adsorbed onto graphene to produce a viable, molecularly specific electrode surface.